ADAPTABILITY AND LEARNING ARE THE MOST IMPORTANT SKILLS IN TEACHING - Khusainova Firuza Tokhirovna; Abutaeva Saparkul Bazarbaevna (Web of Journals Publishing, 2025)
The article reveals the essence of the concepts of «adaptability» and «learning». The main attention is paid to the characteristics of these skills, the targeted formation of which is considered as possible directions for their development in teaching.
Keywords: Successful career, knowledge, experience, development, teacher, soft skills, adaptability, learning, motivation, professionalism.